Ag1+xTlO2 (0.03 ≤ x ≤ 0.18), Novel Adaptations of the Delafossite Structure Type Featuring Subvalent Silver1. Issue 6 (25th February 2014) - Nuss, Jürgen; Dietrich, Volker; Curda, Jan; Jansen, Martin
Abstract A family of novel variations of the delafossite type of structure, Ag1+xTlO2, was synthesized and characterized. For three members the crystal structures were solved and refined on single crystal data: Ag1+αTlO2 [α = 0.18, P <![CDATA[$\bar{3}$]]> <inline-graphic xlink:href="ark:/27927/pgh2sx68mr" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />m1, Z = 1, a = 3.40427(9), c = 6.1296(1) Å, R1 = 0.033, 126 independent reflections]; Ag1+βTlO2 [β = 0.09, R <![CDATA[$\bar{3}$]]> <inline-graphic xlink:href="ark:/27927/pgh2sx68jq" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />m, Z = 6, a = 3.40685(8), c = 37.5953(9) Å, R1 = 0.039, 214 independent reflections]; Ag1+γTlO2 [γ = 0.03, R <![CDATA[$\bar{3}$]]> <inline-graphic xlink:href="ark:/27927/pgh2sx68k7" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />m, Z = 9, a = 3.403(2), c = 56.67(3) Å, R1 = 0.038, 397 independent reflections]. Different from the conventional delafossite structure, part of the silver layers accommodate an excess of ca. 0.18 silver atoms per layer, thus generating a subvalent bonding state of silver. In accordance with the structural findings, the new silver oxthallates(III) are metallic conductors, and show reduced binding energies for the silver 3d5/2 states, compared to silver(I) oxide.